Peran Bank Syariah Dalam Penyaluran Dana Bagi Usaha UMKM di Cikarang - Leli nofentri hulu; Ade Faisal; Tutiek Indriani; Muhamad Syahwildan (STIKes Ibnu Sina Ajibarang, 2025)
The role of Islamic banks in distributing funds to MSMEs in Cikarang is crucial for strengthening the local economy. By offering financing products based on Sharia principles such as murabahah, musharakah, and mudharabah, Islamic banks provide capital solutions for MSMEs while upholding the principles of justice and risk-sharing. A qualitative review of the literature indicates that the involvement of Islamic banks can enhance access to capital, improve business productivity, and foster long-term relationships between banks and entrepreneurs. The main issues identified include a lack of understanding of Sharia principles among MSMEs and credit-related risks. The recommendations from this study include increasing Sharia education, simplifying contractual procedures, and strengthening the role of supporting institutions.